The frequency of autoimmune thyroid disorders in juvenile idiopathic arthritis - Ünsal, Erbil; Ören, Oğuz; Salar, Koray; Makay, Balahan; Abacı, Ayhan; Özhan, Bayram; Böber, Ece (The Turkish Journal of Pediatrics, 2008)
Few studies have been performed to investigate autoimmune diseases associated with organ non-specific rheumatological disorders in children, such as juvenile idiopathic arthritis (IA). The objective in this study was to determine the frequency of autoimmune diseases of the thyroid gland in children with JIA. Eighty patients with JIA and 81 healthy sex- and age-matched controls were enrolled in the study. Serum free T3, free T4, thyroid stimulating hormone (TSH), anti-thyroglobulin antibodies, and anti-peroxidase antibodies were evaluated. The mean age was 11.5 +/- 5.5 years in the patient group and 10.5 +/- 4.9 years in the control group. Twenty-seven of the cases were classified as oligoarticular, 26 as polyarticular, 17 as enthesitis-related, 6 as systemic, and 4 as psoriatic arthritis. Autoimmune thyroid disease was found in 4 patients in the JIA group (5%). There were no significant differences between the study and control groups regarding the existence of anti-thyroid antibodies (p = 0.17). Girls were more likely to develop autoimmune thyroiditis (3 girls, 1 boy). Autoimmune thyroiditis was more frequent in patients who had a family history of thyroid disease (p = 0.02). There was no statistical correlation between rheumatoid factor (RF) and antinuclear antibody (ANA) positivity and autoimmune thyroiditis (p > 0.05). We conclude that there is no need for routine screening of serum thyroid function tests and thyroid antibody levels in patients with JIA in the absence of clinical symptoms.